WASHBACK OF THE PROFICIENCY ASSESSMENT AS EXIT REQUIREMENT ON NON-ENGLISH MAJOR STUDENTS AT A LAW SCHOOL = TÁC ĐỘNG CỦA BÀI ĐÁNH GIÁ NĂNG LỰC TIẾNG ANH CHUẨN ĐẦU RA ĐỐI VỚI SINH VIÊN KHÔNG CHUYÊN KHOA LUẬT - Bùi, Thanh Hường (2020)
With the introduction of the Project 2020, students at most universities in Vietnam have to pass the graduation proficiency assessment. The understandings of the test effects on learning and teaching, or washback, are essential for the teachers, students and test administrators to gain desirable test outcomes. However, little is known about test’s washback, particularly washback on students in Vietnam. This study, hence, investigate the perception of students of a graduation proficiency assessment and the washback of the test on students’s test preparation strategies through questionnaires and interviews. The results show that students have positive perceptions towards the graduation proficiency assessment but the test exerts little effect on their test preparation. Although students of different years share the optimistic attitudes toward the test, they tend to prepare for the test differently. While the seniors study more test-like materials, the freshmen are likely to study general English tasks.